EKSISTENSI PEMERINTAH DALAM PENGALOKASIAN WILAYAH PERTAMBANGAN RAKYAT DI KALIMANTAN BARAT - Ardian Chandra Aji (Media Bina Ilmiah, 2024)
People's mining is expected to have local economic potential that can drive regional economies, suppress and control environmental damage, as well as efforts to cause vertical and horizontal conflicts, wasteful exploitation of mining materials, and regional income, as well as improve the welfare of local communities. The method is carried out by studying literature and documents and going out into the field to conduct interviews as complementary data. The aim of the research is that the existence of People's Mining is a real effort for the existence of the West Kalimantan Provincial Government to facilitate the legalization of people's mining businesses. A determination of People's Mining Areas (WPR) with a mining permit is a company with a cooperative or individual legal entity. From the existing WPR, business actors submit applications to the PERINDAGESDM Department of West Kalimantan Province in accordance with Minister of Energy and Mineral Resources Decree No. 93.K/MB.01/MEM.B/2022 and Law Number 3 of 2020. If compliance is appropriate with regulations, a permit will be processed and issued. People's Mining (IPR) to Cooperatives by the West Kalimantan Province PMPTSP Service via the OSS RBA system as a risk-based business licensing system according to Government Regulation Number 5 of 2021 concerning Implementation of Risk-Based Business Licensing. Community mining that meets formal requirements by establishing ownership of the IPR area. For businesses and/or activities in the People's Mining Area (WPR) for metal commodities (gold) in Kapuas Hulu Regency, there are 6 (six) areas.